2021
DOI: 10.1126/scisignal.abb0969
|View full text |Cite
|
Sign up to set email alerts
|

A leukotriene-dependent spleen-liver axis drives TNF production in systemic inflammation

Abstract: Production of the proinflammatory cytokine tumor necrosis factor (TNF) must be precisely regulated for effective host immunity without the induction of collateral tissue damage. Here, we showed that TNF production was driven by a spleen-liver axis in a rat model of systemic inflammation induced by bacterial lipopolysaccharide (LPS). Analysis of cytokine expression and secretion in combination with splenectomy and hepatectomy revealed that the spleen generated not only TNF but also factors that enhanced TNF pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
1
12
0
3
Order By: Relevance
“…Cagnina et al, recently showed excess TNF production in a CGD mouse model challenged with Aspergillus triggers additional neutrophil recruitment, driving a pro-inflammatory spiral which is responsible for host lung damage [ 41 ]. This supports other research demonstrating exaggerated TNF responses are responsible for host injury [ 163 , 164 ]. ROS are believed to inhibit NF-κB signalling to prevent hyper-inflammation [ 165 , 166 ].…”
Section: Failures Of Innate Immunity In Diseasesupporting
confidence: 91%
“…Cagnina et al, recently showed excess TNF production in a CGD mouse model challenged with Aspergillus triggers additional neutrophil recruitment, driving a pro-inflammatory spiral which is responsible for host lung damage [ 41 ]. This supports other research demonstrating exaggerated TNF responses are responsible for host injury [ 163 , 164 ]. ROS are believed to inhibit NF-κB signalling to prevent hyper-inflammation [ 165 , 166 ].…”
Section: Failures Of Innate Immunity In Diseasesupporting
confidence: 91%
“…Some studies have also shown that the spleen participates in the mucosal immune response in the gut [ 22 , 23 ]. Because intestinal and splenic blood flow forms the portal vein system passing into the liver, the antigens and inflammatory factors from intestinal and splenic blood can enter the liver [ 24 , 25 ]. In addition, the gut and liver communicate via a tight bidirectional connection through the biliary tract [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 It is noteworthy that splenic macrophage-derived leukotriene B4 enhances TNF-α secretion by hepatic Kupffer cells through the portal vein, and that splenectomy inhibits LPS-induced expression of TNF-α in the liver. 29 These findings indicate that spleen-derived humoral factors strongly contribute to the regulation of hepatic inflammation, and that cytokines released by splenic cells may be involved in NASH development.…”
Section: Discussionmentioning
confidence: 86%